Correlation of students' background entry and academic performance in first and second year of UiTM pharmacy students / Muhammad Abdul Rauf Safie - Safie, Muhammad Abdul Rauf (2014)
Each year, Faculty of Pharmacy of UiTM will has a new intake of students from various backgrounds of studies. Among of the students were from Asasi UiTM, Asasi UM, Diploma and matriculation. The study is design to fulfill three objectives which are, to determine either students' background of studies will affect their current performance in degree program. The second objective is to study the correlation either students' CGPA during pre-degree education give an affect towards their current studies. The third and the last objective is to determine either availability of hostel facility occupation by students will has an affect towards students' studies performance. The outcome of this study will be helpful for higher administration of Faculty of Pharmacy to select best pre-education students and for higher administration of UiTM itself either to take in consideration to provide more availability of hostel towards degree students. The study is based on two components, based on students' performance of CGPA during pre-degree education and current degree education. The students' performance was got from administration of faculty and the perception section is based on answer of students from questionnaire given. Based on the result can be concluded that students from different background of studies don't have significant difference in term of their current performance of degree program. Next the result shows that no significance correlation between students' pre-degree performance and their current performance. The result also shown that hostel occupation of students give no significance affect towards students current performance.